The right to game AI-systems: a speculative right for contestation - van den Boom, Freyja (Frontiers in Communication, 2026)
This paper proposes the ‘right to game AI-systems’ as a speculative design artifact to challenge dominant narratives that position ‘gaming’ as a threat to algorithmic integrity. We argue that in high-stakes domains like insurance, health, and welfare, gaming the system should be recognized as a legitimate and necessary act of agency, resistance, and contestation. Rooted in a critical reading of the GDPR and the EU AI Act, and employing Causal Layered Analysis (CLA) and speculative design, we reframe the ‘right to game’ as a vital response to structural opacity and the unequal power dynamics inherent in AI governance. By connecting ‘gaming’ to established concepts of contestability, ethical hacking, and playful exploration, this paper argues for a radical shift in perspective that empowers individuals to become active participants in, rather than passive subjects of, algorithmic decision-making.